"We must be responsible for our children" : the makings of motherhood in Ocean View - O'Rourke, Shannon Laraine (2016)
This thesis explores conceptions and experiences of motherhood in Ocean View, South Africa through the investigation of a maternal and child health intervention. The Moms and Tots support programme seeks to provide mothers with health education and supportive social networks to improve maternal and child health in a resource-poor context. Based on data collected from participant observation and interviews, three major themes have emerged from the research: the framing of Ocean View and its residents within a discourse of deficiency, the responsibilization of the mother, and the demanding nature of care in the face of resource scarcity. Notions of the ideal mother represent a moral discourse around what it means to bring a new life into the world, and who is equipped to do so. I argue that positioning the mother as the site of intervention for improved well-being of future generations underplays the political-economic context that shapes physical, mental, and emotional health in Ocean View. Knowledge interventions that seek to produce behaviour change must focus on the mother's potential rather than risk and adequately acknowledge the constraints in social and material environments if they are to offer viable solutions for health improvement. The Moms and Tots programme plays a vital role in diffusing maternal responsibility through offering social and material networks of support to mothers in Ocean View